POLA PERJALANAN DAN PENGELUARAN WISATAWAN MILENIAL KE BALI - Dewi, LGLK. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 8 No 1 (2020): Jurnal IPTA (July 2020)DO - 10.24843/IPTA.2020.v08.i01.p04, 2020)
The trend of world tourism, especially in the dimension of tourists as travelers. The current phenomenon is that millennial tourists are the most potential types of tourists for Bali tourism at this time. Bali as a central tourist area in Indonesia, and world tourist destinations have the potential to support tourism growth. These potentials include human potential and culture. Beautiful and ideal natural panorama, green forests, mountains, lakes, rivers and rice fields that stretch with terraces and beautiful beaches with a variety of black and white sand. This study aims to determine the trend of millennial tourist trips during their trips in Bali and to find out the travel patterns and spending patterns of millennial tourists during their tour activities in Bali. This study uses descriptive qualitative-quantitative data analysis (mix method). The sample was determined purposively amounting to 100 millennial tourists who traveled to Bali. Data collection techniques are observation, questionnaires, and documentation. The study results show that the pattern of millennial tourists traveling to Bali is that the millennial tourists are tourists who have come more than once, with trips dominated by airplanes to Bali, in their activities tourists prefer social media as a source of information, preferring to take selfies on tourist attraction, use a private rental vehicle. Millennial tourists spending patterns, dominated by accommodation, souvenirs, attractions, rental vehicles and food and beverages. In the selection of accommodation, attractions and food and drinks are more influenced by social media which is the source of his recommendations.